2021
DOI: 10.3390/nu13041299
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Cancer and Diet: An Update

Abstract: Oral cancer, included within head and neck cancer, is the sixth most common malignant neoplasm in the world. The main etiological factors are tobacco and alcohol, although currently, diet is considered an important determinant for its development. Several dietary nutrients have specific mechanisms of action, contributing to both protection against cancer and increasing the risk for development, growth, and spread. Foods such as fruits, vegetables, curcumin, and green tea can reduce the risk of oral cancer, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 96 publications
2
23
0
Order By: Relevance
“…The main risk factors for HNC are tobacco, alcohol, HPV (especially 16, for oropharyngeal carcinoma), Epstein-Barr virus (EBV, for nasopharyngeal carcinoma), and HIV/AIDS; however, an association with hepatitis C and hepatitis B infection, as well as with pro-inflammatory diet (rich in red meat and fried foods) [ 74 , 75 , 76 , 77 , 78 ], has also been observed. Interestingly, evidence suggests a link between the renin–angiotensin system and HNC, and a recent study involving 5000 patients demonstrated that angiotensin II receptor blockers usage is associated with improved overall survival (OS) and cancer-specific survival among HNC patients with chronic kidney disease or hypertension [ 79 ].…”
Section: Head and Neck Cancer Etiopathogenesismentioning
confidence: 99%
“…The main risk factors for HNC are tobacco, alcohol, HPV (especially 16, for oropharyngeal carcinoma), Epstein-Barr virus (EBV, for nasopharyngeal carcinoma), and HIV/AIDS; however, an association with hepatitis C and hepatitis B infection, as well as with pro-inflammatory diet (rich in red meat and fried foods) [ 74 , 75 , 76 , 77 , 78 ], has also been observed. Interestingly, evidence suggests a link between the renin–angiotensin system and HNC, and a recent study involving 5000 patients demonstrated that angiotensin II receptor blockers usage is associated with improved overall survival (OS) and cancer-specific survival among HNC patients with chronic kidney disease or hypertension [ 79 ].…”
Section: Head and Neck Cancer Etiopathogenesismentioning
confidence: 99%
“…However, there are not always satisfactory for HCC targeted therapies in partial patients due to the differences of their clinicopathological features and genes (20). For example, it is well known that alcohol consumption is a risk factor for HCC and other cancers (21)(22)(23)(24)(25), but there are still many unknown molecular mechanisms and prognostic biomarkers in alcoholrelated HCC. Therefore, prognostic biomarkers with higher prediction accuracy in predicting prognosis are urgently needed before detectable clinicopathological abnormalities in treatments of alcohol-related HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, alcohol consumption, poor dental hygiene, the human papillomavirus, and betel nut consumption are most commonly reported risk factors of oral cancer ( 6 12 ). However, in addition to the conventional risk factors described above, other environmental factors including dietary and nutrients have also been reported in recent research ( 13 15 ). The significance of vegetables and fruits abundant in dietary fiber and vitamins in carcinogenesis is garnering more attention among dietary factors ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 88%